Development of Inquiry-Based Teaching Modules in Science and Technology Subjects Creative Economy Material for Phase C at UPT SD Negeri 192 Inpres Tamalalang - Jamaluddin, Jamaluddin; Rahman, Nawir; Hartini, Hartini; Elpisah, Elpisah (CV. Rayyan Dwi Bharata, 2025)
This research is development research (RD) which aims to produce educational products in the form of teaching modules for an independent curriculum that integrates inquiry-based learning. The aim of this research is to describe the profile of the teaching modules developed and produce teaching modules that are valid, practical and effective in learning. The development model used adapts the ADDIE development model with 5 stages. Research subjects included expert validators, science and science teachers as practitioners, and Phase C students at UPT SD Negeri 192 Inpres Tamalalang. The research results show that the validity value obtained from the validator is 4.82 in the very valid category. The practicality of the teaching module based on teacher responses obtained a percentage of 89.67%, which means it is Very Practical and student responses obtained a percentage of 91.11%, which means it is Very Practical. Based on the analysis of learning outcomes using the T test, a significance value (2-tailed) α (0.05) was obtained, which means that there was a real increase in learning outcomes before and after learning using the teaching module developed with an increase in the average student score of 33. 76%. So it can be concluded that the integrated teaching module of the Inquiry learning model developed is valid, practical and effective for use in learning science and science creative economics material in Phase C UPT SD Negeri 192 Tamalalang.